The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.14715/cmb/2020.66.5.1
|View full text |Cite
|
Sign up to set email alerts
|

Importance of miR-125a-5p and miR-122-5p expression in patients with HBV infection

Abstract: MicroRNAs (miRNAs) as a small RNA and post-transcriptional modulator are shown to have regulatory effects for different cellular activities and pathways, such as metabolism, virus replication and also cell growth. In addition, miRNAs can regulate the replication of the hepatitis B virus (HBV). Therefore, the expression profile of miRNAs was evaluated in HBV infected patient groups and healthy controls. The expression levels of following microRNAs (as noninvasive biomarkers) were compared in two experimental (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The result of the survey of miRNA 141-5p expression in patients HBV like miR-NA 501-5p It is not diagnostic value (27). In the study like we found no significant difference between the six miRs (miR-199a-3p, miR-210, miR-205, miR155, miR-372, and miR-1) in the serum of patients infected with HBV compared to the control group (28). Our data indicated that mean ALT and AST were significantly higher (p<0.001) in the EPCH group than in ENCH and OHB and healthy controls, suggesting a positive correlation with hepatic necroinflammation.…”
Section: Discussionmentioning
confidence: 65%
“…The result of the survey of miRNA 141-5p expression in patients HBV like miR-NA 501-5p It is not diagnostic value (27). In the study like we found no significant difference between the six miRs (miR-199a-3p, miR-210, miR-205, miR155, miR-372, and miR-1) in the serum of patients infected with HBV compared to the control group (28). Our data indicated that mean ALT and AST were significantly higher (p<0.001) in the EPCH group than in ENCH and OHB and healthy controls, suggesting a positive correlation with hepatic necroinflammation.…”
Section: Discussionmentioning
confidence: 65%
“…As a result of the evolution of receptors for biological compounds over millions of years, scientists are currently designing hybrid devices using nanoscience and biology, known as Nano-biosensors so that they can detect molecules in extremely small concentrations, inaccessible regions, and even within cells [26] . Small RNAs (miRNAs) have been demonstrated to have regulatory effects on a variety of cellular processes and pathways, including metabolism, viral replication, and cell development [27] . Droplets of varying sizes are the primary means by which the COVID-19 infection spreads.…”
Section: Introductionmentioning
confidence: 99%
“…The limited efficacy is primarily associated with the ability of HBV to evade innate immunity through various mechanisms (3)(4)(5)(6), including destroying the corresponding recognition receptors (7) and depleting the inflammatory factors important for the activation of adaptive immunity (8). Studies on HBV are becoming increasingly diverse, ranging from studies at the molecular and protein level, to studying the impact of the occurrence and development of viral hepatitis (9)(10)(11). However, to the best of our knowledge, only one study (12) has investigated the effects of transcription factors on the invasive activity of HBV in hepatocytes.…”
Section: Introductionmentioning
confidence: 99%